Factors affecting oral health determinants in female university students: a cross-sectional survey in Saudi Arabia - Dar-Odeh, Najla S.; Aleithan, Fatimah Ali; Alnazzawi, Ahmad A.; Al-Shayyab, Mohammad H.; Abu-Hammad, Shaden O.; Abu-Hammad, Osama A. (International journal of adolescent medicine and health, 2017)
Objective This study aims at investigating factors affecting oral health patterns, attitudes and health risk behaviors among female university students. Methods An online questionnaire was distributed to female university students in Al Madinah in the western region of Saudi Arabia. Students were requested to answer questions on demographic data, oral hygiene practices, dental attendance, smoking history, practice of sports and body weight and height. Results Two hundred and fourteen students participated with age range of 18-31 years (mean = 21.64 ± 1.72 years). Oral hygiene habits were reported by a percentage of 97.2%, 34.6%, 30.8% and 19.2% who used a tooth brush, dental floss, mouthwash, and a miswak (a teeth cleaning twig made from the Salvadora persica tree), respectively. The only factor that was significantly associated with a good oral hygiene level was a university major of non-healthcare specialties (p = 0.009). Conclusion It is concluded that female university students use various oral hygiene methods, however, dental attendance is poor and a number of health risk factors are noticed like smoking, lack of practicing sport and unhealthy body mass index (BMI).